Odpowiedzi

2010-04-13T20:30:12+02:00
A) 1/3x - 2=x+2
1/3x -x = 2+2
-2/3x=4|*-3
2x=-12|:2
x=-6

b) 1-6/7x=4/7
1-4/7 =6/7x
3/7=6/7x|*7
6x=3|:6
x=1/2

c) 6(1/4x-2) =18
6/4x-12=18
3/2x=18+12
3/2x=30|*2
3x=60|:3
x=20

d) x/6-1/6=1|*6
x-1=6
x=6+1
x=7

e) -2(2x+1)=x/3
-4x-2=x/3|*3
3(-4x-2)=x
x=-12x-6
x+12x=-6
13x=-6|:13
x=-6/13

f) 2/5(3-x)=-2
6/5-2/5x=-2|*5
6-2x=-10
2x=6+10
2x=16|:2
x=8
g) 3/4(2-3x)=-6
6/4-9/4x=-6|*4
6-9x=-24
9x=6+24
9x=35|:9
x=4

h) 1/5(x-3)=9-x
1/5x-3/5=9-x
1/5x-3/5=9-x|*5
x-3=5(9-x)
x-3=45-5x
x+5x=45+3
6x=48|:6
x=8